2020
DOI: 10.1002/wat2.1471
|View full text |Cite
|
Sign up to set email alerts
|

Historical development of rainfall‐runoff modeling

Abstract: Rainfall‐runoff models are used across academia and industry, and the number and type have proliferated over time. In this primer we briefly introduce the key features of these models and provide an overview of their historical development and drivers behind those developments. To complete the discussion there is a brief section on model choice including model intercomparison. We also seek to clarify jargon terms for readers new to this area. This article is categorized under: Science of Water > Hydrological P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 130 publications
(177 reference statements)
0
17
0
2
Order By: Relevance
“…DL methods have been used in hydrology and meteorology for decades (Daniell, 1991;Halff et al, 1993;Dawson and Wilby, 1998;Wilby et al, 2003;Peel and McMahon, 2020). However, one architecture explicitly designed for time series simulation, the long short-term memory (LSTM) network (Hochreiter et al, 2001;Hochreiter, 1991), has recently demonstrated credible performance for modelling hydrological signatures across the continental United States (CONUS) (Kratzert et al, 2018(Kratzert et al, , 2019Duan et al, 2020;Feng et al, 2020;Gauch et al, 2021b;Fang et al, 2018Fang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…DL methods have been used in hydrology and meteorology for decades (Daniell, 1991;Halff et al, 1993;Dawson and Wilby, 1998;Wilby et al, 2003;Peel and McMahon, 2020). However, one architecture explicitly designed for time series simulation, the long short-term memory (LSTM) network (Hochreiter et al, 2001;Hochreiter, 1991), has recently demonstrated credible performance for modelling hydrological signatures across the continental United States (CONUS) (Kratzert et al, 2018(Kratzert et al, , 2019Duan et al, 2020;Feng et al, 2020;Gauch et al, 2021b;Fang et al, 2018Fang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of some of the bestknown hydrological models at the end of the 20th century can be found in the work by Singh (1995). Peel and McMahon (2020) provide a recent review on the development of runoff models.…”
Section: Catchment Model Developmentsmentioning
confidence: 99%
“…An overview of some of the best-known hydrological models at the end of the 20 th century can be found in the work by (Singh, 1995). Peel and McMahon (2020) provide a recent review on the development of runoff models.…”
Section: Early Types Of Hydrological Modelsmentioning
confidence: 99%